2019
DOI: 10.1021/jacs.9b08818
|View full text |Cite
|
Sign up to set email alerts
|

Cluster–Nuclei Coassembled into Two-Dimensional Hybrid CuO-PMA Sub-1 nm Nanosheets

Abstract: In the sub-1 nm scale region, nanomaterials have shown some novel and interesting chemical and physical properties, such as flexibility, polymer-like rheology, etc. However, how to limit the size of hybrid nanomaterials into sub-1 nm scale is still a great challenge. Herein, by incorporating phosphomolybdic acid (PMA) clusters into inorganic materials (CuO) during the nucleation step, we first synthesized the twodimensional (2D) hybrid CuO-PMA sub-1 nm nanosheets (SNSs). Molecular dynamics (MD) simulations dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 36 publications
2
63
0
Order By: Relevance
“…The peaks at 780.95 eV and 796.95 eV in both spectra could be attributed to Co II 2p 3/2 and 2p 1/2 , respectively. [39] The Mo 3d spectrum (Figure 2 b) exhibits two typical peaks at 232.2 eV and 235.4 eV which could be assigned to 3d 5/2 and 3d 3/2 respectively, manifesting a typical Mo VI signal, [35,40] which further confirms the existence of POM in the material.…”
mentioning
confidence: 60%
“…The peaks at 780.95 eV and 796.95 eV in both spectra could be attributed to Co II 2p 3/2 and 2p 1/2 , respectively. [39] The Mo 3d spectrum (Figure 2 b) exhibits two typical peaks at 232.2 eV and 235.4 eV which could be assigned to 3d 5/2 and 3d 3/2 respectively, manifesting a typical Mo VI signal, [35,40] which further confirms the existence of POM in the material.…”
mentioning
confidence: 60%
“…It demonstrated that protonated oleylamine molecules (OLY) were used to neutralize the total charge of the system and CuO molecules interacted with PMA clusters to co-assemble into 2D simple square SNSs, which can keep stable. In this work, we firstly prepared the 2D hybrid CuO-PMA SNSs according to the last work, 27 and on the basis of MD simulations about the CuO-PMA SNSs, we continued to try to study the interaction between Ag NPs and CuO-PMA SNSs in the CuO-PMA-Ag THSNHs by taking advantage of MD simulations. Firstly, in order to investigate the coaction of Ag NPs and CuO-PMA SNSs, 16 Ag NPs capped by oleylamine (OLL) were placed at the surrounding of 25.2 nm * 24.5 nm CuO-PMA SNSs as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…25 In this strategy, well-defined polyoxometalate (POM) clusters were introduced to intervene the nucleation of inorganic materials at the nucleation stage, where size-matched clusters interacted and co-assembled with inorganic nuclei to grow into different kinds of nanomaterials with sub-1 nm structures. Until now, we have successfully synthesized hybrid one-dimensional (1D) sub-1 nm nanobelt superstructures, 26 2D sub-1 nm nanosheets 27 and 3D assemblies, 25 etc., which performed highly efficient energy conversion, outstanding catalytic activity, etc. Metal-oxide nanoheterostructures usually possess performances of metals and oxides leading to more research interests.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, the rapid growing demand for mobile power has prompted researchers to continually explore energy storage technologies to obtain energy storage devices with excellent power and energy density. There are two main electrical energy storage (EES) devices including batteries and supercapacitors [166][167][168][169]. The performance of EES is bound up with the electrode materials driving researchers to find suitable electrode materials.…”
Section: Mof and Cof Nanosheets For Energy Storagementioning
confidence: 99%